(untitled) (Seminar_BG, 2023)
This study presents an interdisciplinary analysis of the local Macedonian music scene in the last decade by analyzing musical projects inspired by the political actions of the largest and ruling parties VMRO-DPMNE and SDSM. The research is based on an analysis of music albums or songs from the field of contemporary and indie music, realized in the last ten years and directly inspired by specific political events. The results of the study shaped several levels of action from musicians with the purpose to express their critical opinion on political events through the relationship of music with politics, memory, gender, and culture. References Atali, Žak. 2007. Buka. Beograd: Biblioteka XX vek. Boym, Svetlana. 2001.The Future of Nostalgia. New York: Basic Books. Deleuze, Gilles. 2004. Difference and Repetition. London, New York: Continuum. Dimkov, Toni. 2016. „Bernaјs propaganda: Politika e za apsolutnoto mnozinstvo vo ovaa zemјa so grubi pluskavtsi i tsrno pod noktite“. MKD (last seen 7.01.2023.). Dimov, Ventsislav. 2019. Muzikata za naroda na mediynia front (Mekata vlast na narodnata i populyarna muzika v Sotsialisticheska Bulgaria). Sofia: UI „Sv. Kliment Ohridski“. Dimov, Ventsislav. 2020. „Etnopop muzika i vlast na Balkantite (kak edna hibridna muzika stava meka sila v kulturnite voyni: mediyno-antropologicheski prochiti)“. In: Peycheva, Lozanka (sast. i red.) Mekata vlast na populyarnata muzika v mediite (po primeri ot Bulgaria i Balkanite). Sofia: UI „Sv. Kliment Ohridski“, 12–63. Grigorov, Grigor. 2017. „Gradat kato tekst: semantika na simvolichnite prostranstva, oformeni chrez izgradenite po proekt „Skopie 2014“ pametnitsi“. In: Peycheva, Lozanka, Grigor Grigorov (sast.) Proektsii na kulturnite traditsii: Bulgaria-Makedonia. Sofia: Izdatelstvo na BAN „Prof. Marin Drinov“, 27–74. Grossberg, Lawrence. 2010. Cultural Studies in the Future Tense. Durham and London: Duke University Press. Grossberg, Lawrence.1983. „The Politics of Youth Culture: Some Observations on Rock and Roll in American Culture“. Social Text, 2: 104–126. Јordanovska, Meri. 2015. „Skopјe 2014 dostigna nad 600 milioni evra“. Prizma : internet stranitsa, za promotsiјa i јakneњe na istrazhuvachkoto novinarstvo. (last seen 7.01.2023.). Kundera, Milan. 1990. The Book of Laughter and Forgetting. New York: Penguin. Levi, Kler. 2012. Muzikalnata parodia v kraya na 20 i nachaloto na 21 vek. Sofia: Institut za izsledvane na izkustvata–BAN. Middleton, Richard. 2013. Voicing the Popular: On the Subjects of Popular Music. London, New York: Rutledge. Mišina, Dalibor. 2013. Shake, Rattle and Roll: Yugoslav Rock Music and the Poetics of Social Critique. Ashgate. Papazova, Julijana. 2017. Alternative Rock in Yugoslavia 1980-1991. Berlin: LAP. Papazova, Julijana. 2018. „Poglednaženskost v ustvarjalnostiskladareljic v Republiki Makedoniji“. In: Stefanija, Leon, Bogunović Hočevar, Katarina (eds.). Ženskost v glasbiskladateljic po 1918 Pogledinekaterihmanjšihglasbenih kultur Evrope. Femininity in the female music since 1918 Views of some smaller musical cultures in Europe. Ljubljana: University, Faculty of Philosophy, 39–54. Papazova, Јuliјana. 2016. „Meѓu muzikata i memoriјata: dozhivuvaњe na proektot „Skopјe 2014“. In: Todorchevska, Jelitsa i Opetcheska-Tatarchevska Ivona (ured.) Zbornik na Strushka muzichka esen – 40 godini „Strushka muzichka esen“, Memoriјa i perspektivi. Skopјe: SOKOM, 155–165. Peycheva, Lozanka (sast. i red.) 2020. Mekata vlast na populyarnata muzika v mediite (po primeri ot Bulgaria i Balkanite). Sofia: UI „Sv. Kliment Ohridski“. Rosić, Branko. 2015. „Mustra za revoluciju, SrđaPopović“. Nedeljnik, 193: 55. Schiffer, Sheldon. 2010. „The Cover Song as Historiography, Marker of Ideological Transformation“. In: Plasketes George (ed.) Play it Again: Cover Songs in Popular Music. Ashgate, 77–98. Street, John. 2001. „Rock, Pop and Politics“. In: Frith, Simon, Straw, Will, Street, John (eds.). The Cambridge Companion to Pop and Rock. Cambridge: Cambridge University Press, 243–255.